S4 Anti-Inflammatory Effects of Vitamin D Are Influenced More by Genetic Background Than Mycobacterial Infection. (19th November 2012) - Hawthorne, G; Mujakperuo, H; Lax, S; McGowan, L; Kunst, H; Thickett, D; Turner, A
Abstract : Introduction: Although vitamin D has antimicrobial effects that may be beneficial in mycobacterial infection, supplementation trials have been disappointing [1]. Response to vitamin D is heterogeneous, perhaps due to genetic variants in the vitamin D axis (vitamin D binding protein; GC or vitamin D receptor; VDR ). We aimed to assess stability and magnitude of anti-inflammatory effect of vitamin D in vitro in mycobacterial infection and health, and the influence of GC and VDR variants. Methods: Peripheral blood monocytes from healthy controls (n=20) and patients with mycobacterial infection (n=8) were cultured and incubated with LPS (100 ng/ml), 25(OH)D3(50 nmol) and 1, 25(OH)2D3(50 nmol). IL6 in cell supernatants was measured by ELISA. Taqman was used to type 4 SNPs: rs7041 & rs4588 ( GC ), rs2228570 & rs1544410 ( VDR ). The effect of the protein product of GC in culture was assessed by addition of plasma and subsequent Luminex array. Results: Change in IL6 between pairs of repeated cultures did not vary (p=0.21), indicating stability of response to LPS. There was no difference between HCs and patients in response to vitamin D (both p>0.32), however in both groups there were responders (n=7 controls, n=5 TB), in whom IL6 fell with addition of vitamin D (1, 25D, p=0.001; 25D, p=0.02) and non-responders (n=11 controls, n=3 TB) in whom it did not. Response to 1, 25D was influenced by rs7041 (T allele; p=0.04), and tended to associate with GC2 (p=0.06). Response to 25D was not affected by genotype until plasma was added when GC haplotype appeared to have an effect. There was no influence of VDR SNPs. Conclusion: Anti-inflammatory effects of vitamin D are influenced by GC genotype in vitro, consistent with previous mouse work [2], however it is unclear whether this occurs in humans in vivo. Such effects are equally relevant in health and mycobacterial infection. Further work to characterise changes in LPS responsiveness following high dose vitamin D replacement is ongoing. Martineau AR, et al. Lancet. (2011) 377:242–50. Zella LA, et al. Endocrinology. (2008) 149:3656–67.